Development of an Online Learning Platform for University Pedagogical Studies-Case Study - Samuli Laato; Heidi Salmento; Mari Murtonen (Portugal, 2022)
Due to a high demand of university pedagogical staff development courses in our university, we were faced with the problem of not being able to offer university pedagogy courses for everyone who wanted to study them. Additionally, we wanted to seek ways to improve our already existing teaching. As a solution, we created a web based learning platform called UTUPS (University pedagogical support). The platform allows us to reach a wider audience and offer courses more conveniently to our teaching staff. Since the platform was released in Autumn 2015, offered modules have been completed cumulatively over 300 times. We propose a learning environment like UTUPS can significantly increase the flexibility and scale of studies that a university can offer. We will provide a thorough explanation on why and how the environment was made, a technical description of the current UTUPS platform, compared it to already existing solutions and analyse its strengths and weaknesses. In order to evaluate the platform, we will utilize primarily student feedback and refer to literature and existing solutions when relevant.
Proceedings of the 10th International Conference on Computer Supported Education - Volume 2: CSEDU